Study on the correlation between total cerebral small vessel disease score and lacunar infarction - Sanqi Wang; Lijun Liu; Qingtang Meng; Xiaohang Su; Xinyu Zhou; Jijun Teng (Frontiers in Neurology, 2025)
ObjectiveTo investigate the relationship between the total cerebral small vessel disease (CSVD) burden and the occurrence of first-ever and recurrent lacunar infarction (LI).MethodsThis study included 271 patients with first-ever acute cerebral infarction hospitalized in the Department of Neurology, Affiliated Hospital of Qingdao University, between January 2019 and January 2024. The total CSVD score was calculated based on imaging findings. Patients were classified into LI and large-artery atherosclerosis (LAA) groups according to infarct size and large-vessel stenosis severity. The LI group was further subdivided into recurrence and non-recurrence subgroups. Clinical and imaging data were compared between groups. Logistic regression was used to identify risk factors for first-ever and recurrent LI, and the predictive value of the total CSVD score for LI recurrence was assessed using receiver operating characteristic (ROC) curve analysis.ResultsThe LI group comprised 153 patients (56.46%), and the LAA group included 118 patients (43.54%). Significant differences were observed in systolic blood pressure (SBP), diastolic blood pressure (DBP), uric acid (UA), albumin (ALB), triglycerides (TG), fibrinogen (FIB), total protein (TP), white matter hyperintensities (WMH), enlarged perivascular spaces (EPVS), lacunar, and total CSVD score between groups (p < 0.05). Logistic regression identified total CSVD score, WMH, EPVS, and UA as independent risk factors for first-ever LI, while FIB acted as a protective factor (p < 0.05). Among 140 LI patients, 28 experienced recurrence. Recurrent LI patients exhibited higher rates of smoking, WMH, EPVS, cerebral microbleeds (CMB), and total CSVD score compared to non-recurrent cases (p < 0.05). ROC analysis demonstrated that the total CSVD score predicted LI recurrence with the area under the curve (AUC) of 0.832.ConclusionThe total CSVD burden correlates with both first-ever and recurrent LIs. It is an independent risk factor for LI and may predict LI onset and progression.